Sosialisasi Pemanfaatan Minyak Jelantah Menjadi Lilin Aromaterapi Di Desa Sungai Rambai Kecamatan Senyerang Kabupaten Tanjung Jabung Barat - Ikhfa Murdi Prayogi; Mikho Riski Indrawan; Muhammad Ermulan; Anggia Fisi Lestari; Sinta; Yesa Adella (PT. Saha Kreasi Indonesia, 2025)
This community engagement initiative aims to build students’ understanding, skills, and awareness regarding the proper management of used cooking oil by converting it into aromatherapy candles. In many households, used cooking oil is commonly discarded in ways that harm the environment, such as pouring it into waterways or soil. To address this issue, the program introduced a series of activities consisting of preliminary observations, informational sessions, and practical workshops. Through these stages, students learned about the environmental risks associated with improper disposal and explored the potential of transforming used oil into useful and marketable products. The outcomes indicate a notable improvement in students’ knowledge and hands-on abilities, particularly in filtering, refining, blending materials, and molding aromatherapy candles. The final products showed good stability, appealing fragrances, and varied forms based on students’ creativity. Beyond increasing environmental awareness, the program also supports the development of simple entrepreneurial opportunities through waste-based innovations. Overall, this activity demonstrates an effective approach to environmental education that combines practical experience with sustainable creativity.